2017
DOI: 10.1021/acsami.7b05740
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin-Loaded Thermosensitive Hydrogel for Long-Term Antiosteopenia Therapy

Abstract: Effective antiosteopenia therapy can be achieved by designing long-term protein/peptide drug delivery systems for bone trabecula restoration. Here we show that a complex of salmon calcitonin and oxidized calcium alginate (sCT-OCA) was prepared and loaded into a thermosensitive copolymer hydrogel for long-term antiosteopenia treatment. The triblock copolymer, poly(d,l-lactic acid-co-glycolic acid)-b-poly(ethylene glycol)-b-poly(d,l-lactic acid-co-glycolic acid) (PLGA-PEG-PLGA) exhibited sol-gel transition at bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 57 publications
1
65
0
Order By: Relevance
“…From this initial study, further testing using sCT was explored in this research using the insight gained. 45 Both lysozyme and sCT retained bioactivity as evidenced by CD, MALDI-TOF mass spectroscopy, and HPLC analysis of entrapped and released therapeutic, demonstrating the ability of the copolymer to protect the structure of sensitive protein and peptide-based therapeutics. Release of therapeutics was observed over the course of 28 and 42 days for lysozyme and sCT, respectively.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…From this initial study, further testing using sCT was explored in this research using the insight gained. 45 Both lysozyme and sCT retained bioactivity as evidenced by CD, MALDI-TOF mass spectroscopy, and HPLC analysis of entrapped and released therapeutic, demonstrating the ability of the copolymer to protect the structure of sensitive protein and peptide-based therapeutics. Release of therapeutics was observed over the course of 28 and 42 days for lysozyme and sCT, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…They found that in vivo in rats over 30 days that the treatment was effective in decreasing serum calcium and bone reconstruction while under glucocorticoid-induced osteopenia. 45 In addition, Li et al were able to investigate a supramolecular nanoparticle of a dipeptide (Asp–Phe, DF) that was complexed with sCT in vitro and in vivo. Release of over one month showed promise as a system that can bypass polymeric materials.…”
Section: Discussionmentioning
confidence: 99%
“…Nanogels can be one of the excellent candidates for SRNAGs. Nanogels or hydrogel nanoparticles have the ability to encapsulate different biologically active molecules such as drugs, proteins, and genes and can be programmed to release the cargo via different external stimuli, such as light, ultrasound, electric field, and magnetic field or internal stimuli, such as pH, temperature, enzymes, and redox potential …”
Section: Discussionmentioning
confidence: 99%
“…They prepared hCT-cucurbit 7 (CB7) complex (cucurbit 7 is an amphiphilic small molecule) to inhibit the fibrillation of highly amyloidogenic hCT by CB7, then incorporated the hCT-CB7 complex into PLGA-PEG-PLGA hydrogel. As another example, a delivery system for salmon calcitonin (sCT), a bioactive peptide to regulate serum calcium concentration by a therapeutic effect to improve bone mass and relieve osteoporotic bone pain, for long-term anti-osteopenia treatment was investigated by Liu et al [48]. They prepared a complex of sCT and oxidized calcium alginate (OCA), a negatively charged polyelectrolyte, to stabilize sCT and control its affinity, then incorporated the sCT-OCA complex into PLGA-PEG-PLGA hydrogels.…”
Section: Applications Of Thermoresponsive Hydrogels Using Block Copolmentioning
confidence: 99%